Aprendizagem motora: papel do cerebelo na prática aleatória e constante - Simone de Menezes Pinto (2019)
Studies have shown that constant practice provides the learning of the relative dimension of motor skills, benefiting the acquisition of a consistent behavior. On the contrary, random practice favors the learning of the skills’ absolute dimension by providing a flexible behavior. Acquisition of these two characteristics defines a skilled behavior. Nowadays, studies are investigating not only the behavioral aspects, but also the neurobiological aspects involved in practice scheduling. A neural structure that plays a relevant role in motor learning is the cerebellum, which has also been associated with practice scheduling, since it participates in learning by updating motor commands through error correction or contextual demands. Thus, one way to investigate this relationship is by using cerebellar transcranial direct current stimulation (tDCS). Despite evidences of cerebellum involvement in less repetitive practice, studies have not investigated how the cerebellum participates in the learning of the relative and absolute dimensions in random and constant practice of motor sequencing tasks. This study was conducted with two experiments. The aim of experiment I was to verify the participation of the cerebellum in the learning of absolute and relative dimensions in random practice of a motor sequencing task. Experiment II was conducted with constant practice to investigate the same issue. Thirty students of both sexes were included in each experiment, with mean age of 22.67 ± 4.41 years in experiment I, and 24.23 ± 5, 56 years in experiment II. Participants performed 120 trials during the acquisition phase on the first day, and 12 trials on each learning test, that were performed 24 hours after acquisition. The results of experiments Iand II demonstrated that cerebellar inhibition did not interfere in the learning of the absolute dimension in random and constant practice of a motor sequencing task. However, in relation to the relative dimension, the cerebellar inhibition favored the learning of this dimension in constant practice, such as observed in off-line learning1 and2. In random practice, cathodal cerebellar stimulation benefited the process of acquisition of the relative dimension of a sequential task, as evidenced by the greatest change during online learning. However, there was no interference in learning. It is possible to conclude that, in general, the cerebellum has no evident participation in the learning of the absolute and relative dimensions in random and constant practice of a motor sequencing task.